2023
DOI: 10.1002/aocs.12696
|View full text |Cite
|
Sign up to set email alerts
|

Fluidized bed roasting modifying the microstructure of cocoa nibs and improving cocoa butter quality

Abstract: The extraction of butter from cocoa seeds involves various processing steps that weaken the lipid‐storing cell walls of cocoa cotyledons. Roasting is particularly critical, making cocoa nibs porous and brittle. In this study, the degree of disruption of the microstructure of cocoa nibs, and the quality and aroma profile of cocoa butter, were evaluated using two roasting techniques, forced convective oven, and fluidized bed. Fluidized bed roasting, recognized for its energy efficiency and low‐carbon footprint, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
(61 reference statements)
1
4
0
Order By: Relevance
“…In other words, the balance between the release and the degradation of Leu, Phe, and Val was in favor of the degradation under the fluidized bed technique, probably toward the formation of MR products such as volatile organic compounds. This hypothesis is supported by our previous studies, , which reported higher formation of pyrazines by the fluidized bed technique than by traditional oven roasting.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…In other words, the balance between the release and the degradation of Leu, Phe, and Val was in favor of the degradation under the fluidized bed technique, probably toward the formation of MR products such as volatile organic compounds. This hypothesis is supported by our previous studies, , which reported higher formation of pyrazines by the fluidized bed technique than by traditional oven roasting.…”
Section: Resultssupporting
confidence: 85%
“…In contrast, oven roasting is mainly based on conductive heat transfer from the metallic surface of the trays, thus resembling the traditional cocoa roasting. In our previous studies, , we found that the heat transfer efficiency of fluidized bed roasting reduced the roasting time by a factor of 12 compared to traditional roasting. As a consequence, fluidized bed roasting led to (i) a higher porosity, thus suggesting a deeper heat penetration within cocoa nibs and (ii) a lower reduction in water activity, which favored the formation of nitrogen-heterocyclic compounds such as pyrazines.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations